Unconditionally stable LOD-FDTD method for 3-D maxwell's equations - Tan, Eng Leong (2020)
This letter presents an unconditionally stable locally 1-D finite-difference time-domain (LOD-FDTD) method for 3-D Maxwell's equations. The method does not exhibit the second-order noncommutativity error and its second-order temporal accuracy is ascertained via numerical justification. The method also involves simpler updating procedures and facilitates exploitation of parallel and/or reduced output processing. This leads to its higher computation efficiency than the alternating direction implicit and split-step FDTD methods.